نوازل زینة المرأة في الفقھ الإسلامي - أحكام الشعر نموذجا - هايشة, سامية (University of Eloued-جامعة الوادي, 2015)
This note deals with the subject of the cataclysms of Muslim Women's Accessories generally and related provisions and devoted to developments in poetry, came outlined its provisions when all the schools of Islamic jurisprudence, and based on this research to the fatwas applicants scientists of them latecomers, and those emerging issues addressed by the note are: developments in the hair, such as Wig haircutting and planted by modern pigments, and developments such as facial hair plucking the eyebrows and eyelashes Bleaching industrial, and recent developments of body hair such as hair removal from the body, modern medical techniques to remove.
مذكرة ماستر
Keywords: النوازل/زینة المرأة /الفقھ الإسلامي/أحكام الشعر; Calamities / women's adornment / Islamic jurisprudence / provisions of poetry